Meteorological Data Forecast using RNN - Balluff, Stefan; Bendfeld, Jörg; Krauter, Stefan (Deep Learning and Neural Networks)
Gathering knowledge not only of the current but also the upcoming wind speed is getting more and more important as the experience of operating and maintaining wind turbines is increasing. Not only with regards to operation and maintenance tasks such as gearbox and generator checks but moreover due to the fact that energy providers have to sell the right amount of their converted energy at the European energy markets, the knowledge of the wind and hence electrical power of the next day is of key importance. Selling more energy as has been offered is penalized as well as offering less energy as contractually promised. In addition to that the price per offered kWh decreases in case of a surplus of energy. Achieving a forecast there are various methods in computer science: fuzzy logic, linear prediction or neural networks. This paper presents current results of wind speed forecasts using recurrent neural networks (RNN) and the gradient descent method plus a backpropagation learning algorithm. Data used has been extracted from NASA's Modern Era-Retrospective analysis for Research and Applications (MERRA) which is calculated by a GEOS-5 Earth System Modeling and Data Assimilation system. The presented results show that wind speed data can be forecasted using historical data for training the RNN. Nevertheless, the current set up system lacks robustness and can be improved further with regards to accuracy.

Numerical Investigation of the Temperature Distribution in PCM-integrated Solar Modules - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny (Chemical Engineering Transactions)

An Automated Solar-Biomass Hybrid Dryer System for Rural Communities in Ghana - Obeng-Akrofi, George; Oppong Akowuah, Joseph; Opoku-Agyemang, Gifty; Nkrumah, Isaac; Donkor, Micheal K. E.; Tamakloe, Reuben Y.; Ampong, Francis K.; Klaus, Tobias; Krauter, Stefan; Waldhoff, Maike; Olenberg, Alexander; Kenig, Eugeny (Proceedings of SWC2017/SHC2017)

Simple and effective methods to match photovoltaic power generation to the grid load profile for a PV based energy system. - Krauter, Stefan (Solar Energy)

Smart charging management system of plugged-in EVs based on user driving patterns in micro-grids - Ameli, Ali; Krauter, Stefan; Ameli, Mohammad Taghi; Moslehpour, Saeid (International Journal of Engineering Research & Innovation)

Photovoltaic yield prediction using an irradiance forecast model based on multiple neural networks - Durrani, Saad Parvaiz; Balluff, Stefan; Wurzer, Lukas; Krauter, Stefan (Journal of Modern Power Systems and Clean Energy)

Lifetime Extension of Photovoltaic Modules by Influencing the Module Temperature Using Phase Change Material - Weber, Daniel; Rafsan Jani, Mohammad Iffat; Grabo, Matti; Wallscheid, Oliver; Klaus, Tobias; Krauter, Stefan; Böcker, Joachim (World Conference on Photovoltaic Energy Conversion (WCPEC-7), 45th IEEE PVSC, 28th PVSEC, 34th EU PVSEC.)

Start-up factory Ghana: Creating an enabling environment for the dissemination of renewable energies - Klaus, Tobias; Nkrumah, I.; Donkor, M.K.E; Tamakloe, R.Y.; Ampong, F.K.; Krauter, Stefan (Proceedings of the ISES Solar World Congress 2017)

Minimizing storage costs by substituting centralized electrical storage by thermal storage at the end user, also suppling balancing power for grid operation - Krauter, Stefan; Prior, Dirk (Energy Procedia)
Many processes in industrial and domestic applications require heating or cooling at certain steps of a process. Even if the process itself cannot be shifted towards periods of high PV output (which would be favorable), the heating and cooling necessities can be carried out via an inexpensive thermal storage instead of a costly electrical storage. Examples are: distillation units, washing machines, dishwashers, coolers, freezers. The resulting “shiftability” of power consumption can be a business model by offering that availability of load dispatching on the balancing power market. An example using PCM as cooling storage for refrigerators that has been investigated: A focus of this paper is the use of that load shifting ability to provide balancing power. Another emphasis is on the protection of individual consumer data: To keep the state of use of each individual consumer (actually: interactive consumer or “prosumer”) anonymous, but still performing the sales of balancing power, the orders for load-dispatching can be transmitted via transmitted via a regional, non-individual broadcasting message within the GSM network. Demonstrating DSMs capacities, abilities and limits concerning domestic applications is an important task to prepare large-scale implementation and to convince stakeholders. To reaching that goal, several realistic DSM scenarios for cooling applications and freezers have been developed with the prerequisite that DSM activities are supposed to be without comfort losses and without restrictions for consumers while the limits for lower and upper temperature for food are maintained.
Keywords: DSM; load management; load shifting; PCM; thermal storage; balancing power

Performance of MERRA2 Data Compared to Floating LiDAR - Bendfeld, Jörg; Balluff, Stefan; Wübbeke, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2017)

Short-term wind speed and power prediction for offshore wind farms using neural networks - Bendfeld, Jörg; Balluff, Stefan; Krüger, J.; Krauter, Stefan (Proceedings of the DEWEK 2017)

Update on rankings of conversion efficiencies and energy yield of micro-inverters, including inverters for two PV modules - Bendfeld, Jörg; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017, S. 1477–1481)

Long-term performance of PV micro-inverters - Bendfeld, Jörg; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017, S. 1836–1840)

Advanced PV Module Hot Spot Characterisation - Krauter, Stefan; Wendlandt, S.; Süthoff, L.; Berendes, S.; Teubner, J.; Podlowski, L.; Berghold, J.; Grunow, Paul (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017)

Comparison of Conversion Efficiencies and Energy Yields of Micro-Inverters for Photovoltaic Modules - Krauter, Stefan (VDE-Proceedings of NEIS 2017 – Conference on Sustainable Energy Supply and Energy Storage Systems by IEEE-PES. Hamburg (Deutschland), 21.–22. September, 2017.)

Smart Charging Management System of Plugged-in EVs for Optimal Operation of Future Power Systems. - Krauter, Stefan; Ameli, Ali (VDE-Proceedings of NEIS 2017 – Conference on Sustainable Energy Supply and Energy Storage Systems by IEEE-PES. Hamburg (Deutschland), 21.–22. September, 2017.)

Minimizing storage costs: Simple and effective methods to match PV with grid load, including shift of holiday period - Krauter, Stefan (Proceedings of the 11th International Conference for Renewable Energy Storage, 14-16 March 2017, Düsseldorf, Germany.)

Introduction of an Advanced Method for Testing of Battery Charge Controllers for Off-Grid PV Systems - Khatibi, Arash; Bendfeld, Jörg; Bermpohl, Wolfgang; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017)

Testing and Analysis of Battery Charge Controllers for Off-Grid PV Systems - Khatibi, Arash; Bendfeld, Jörg; Bermpohl, Wolfgang; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017)

Offshore Metocean Station for Energy Purposes - Balluff, Stefan; Bendfeld, Jörg (Journal of Sustainable Development of Energy, Water and Environment Systems)

Einbindung von Oﬀshore Windenergie durch innovative Prognosemodelle und Speichertechnologien - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (14. Symposium Energieinnovation 2016)

Green Energy from the Ocean An overview on costeffectiv and reliable measuring systems - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Bestimmung der relevanten klimatologischen Parameter Oﬀshore - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Wissenschaftliche Verhandlungen 2016 der Deutschen Physikalischen Gesellschaft Regensburg)

Systemvergleich zur zeitlich und örtlich hochaufgelösten Einstrahlungsmessung - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Wissenschaftliche Verhandlungen 2016 der Deutschen Physikalischen Gesellschaft Regensburg)

Shadowing Investigations on Thin Film Modules - Krauter, Stefan; Wendtland, S.; Weber, T.; Berghold, J.; Grunow, Paul (Proceedings of the 31st European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 20.–24. Juni 2016, S. 2265–2270.)

Start-Up Factory Kumasi (Ghana) – Paderborn (Germany): Smart Tropical House KNUST, Kumasi, Ghana - Klaus, Tobias; Schmitz, E.A.; Klusmann, B.; Piper, M.; Krauter, Stefan; Rongen, L.; Gruber, R.; Nkrumah, I.; Ampong, K.; Donkor, M.; Tamakloe, R. (Proceedings of the 31st European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 20.–24. Juni 2016, S. 3048–3049)

Deviations of results for energy yield from efficiency rankings of micro-inverters - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 31st European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 20.–24. Juni 2016, S. 1508–1511)

Photovoltaics and the Energy System: Adaptation of layout and load. - Kazmerski, L.; Renne, D; Kazem, H.; Sopian, D.K.; Al-Bastaki, N.; Haji, S.; Mohd, D.; Othman, Y.H.; Hoffmann, W.; Krauter, Stefan; Swift-Hook, D.T.; Book, T. (Renewable Energy in the Service of Mankind Vol II)

Experimental study of phase change materials for photovoltaic modules: Energy performance and economic yield for the EPEX spot market - Japs, Ewald; Sonnenrein, Gerrit; Krauter, Stefan; Vrabec, Jadran (Solar Energy)

Short term wind and energy prediction for offshore wind farms using neural networks - Balluff, Stefan; Bendfeld, Jörg; Krauter, Stefan (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Measurement and Analysis of oﬀshore fog occurrences - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 95th AMS Annual Meeting)

Messtechnisches Prinzip eines neuen Einstrahlungsmessgerätes - Bendfeld, Jörg; Balluff, Stefan; Bermpohl, Wolfgang (Wissenschaftliche Verhandlungen 2015 der Deutschen Physikalischen Gesellschaft)

Performance of MERRA Data in Oﬀshore Wind Energy Applications - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Advanced Integration of Oﬀshore Wind Energy into the Grid System by Power to Gas - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Comparison of micro inverters based on practical analysis - Sadati, A.M.; Krauter, Stefan; Bendfeld, Jörg (2015 5th International Youth Conference on Energy (IYCE))

Effective large-scale PV integration: Methods to match load profile with actual PV output - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Assessment of renewable energy resources in cameroon and special regards on energy supply - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Assessment of renewable energy resources and the use of hydro power for fluctuation compensation in Cameroon - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Cost, performance, and yield comparison of eight different micro-inverters - Krauter, Stefan; Bendfeld, Jörg (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

BOS cost reduction via direct PV charging of electrical vehicles - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Stabilizing oﬀshore wind farm power feed-in via power to gas storage systems - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Discovering the potential for oﬀshore windfarms trough measurements - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Wind power forecasting for oﬀshore wind farms - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore wind energy development based on Merra data - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore metocean station for energy purposes - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Short term wind and energy prediction for oﬀshore wind farms using neural networks - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (EWEA Forecasting 2015 Technology Workshop)

Integration of Wind Energy in Power System—Modelling of a Market Oriented Energy Concept - Bouyraaman, Yassin; Bendfeld, Jörg; Breymann, Philipp; Krauter, Stefan (Renewable Energy in the Service of Mankind Vol I)

Integration of offshore wind energy into the grid system in Germany: Modelling of a market oriented energy provision - Bouyraaman, Yassin; Bendfeld, Jörg; Krauter, Stefan (14th IAEE European Energy Conference- Sustainable Energy Policy and Strategies in Europe, Rome, Italy, October 28-31, 2014)

Integration of wind energy in power systems: Modeling of a market-orientated energy concept - Bouyraaman, Yassin; Bendfeld, Jörg; Krauter, Stefan; Breymann, P. (Proceedings of the World Renewable Energy Congress WREC XIII, London, (UK), August 3-8, 2014)

Reduction of Offshore Wind farm power Feed-in ﬂuctuations via Power to Gas Storage Systems - Bouyraaman, Yassin; Bendfeld, Jörg (Solar 2014/Intersolar North America, San Francisco, July 6-10, 2014)